Entrepreneurship motivation among accounting students : the role of financial literacy and financial behaviour - Noor Lela Ahmad,; Nadiah Farhanah Mohd Fazil,; Bazri Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study explores the effects of financial literacy and financial behaviour on entrepreneurial motivation among accounting students in Malaysia’s public universities. University students’ financial literacy level and financial behaviour level are also explored. This study employed a quantitative survey method and used twenty financial items and ten entrepreneurship motivation items to answer the research questions. A total of 530 accounting undergraduates from three public universities in Malaysia were given a financial and entrepreneurial test. To get results, data were analysed using mean and frequency analysis, a reliability test, Pearson’s product-moment analysis and regressions. Our findings demonstrated that the accounting students’ financial literacy and financial behaviour was at a moderate level. However, accounting students possessed a high level of entrepreneurship motivation. Supporting past research, this study found that financial literacy and financial behaviour affect accounting students’ entrepreneurial motivation. This research has valuable implications for educators, higher education and policymakers by designing a more integrated education curriculum and effective policy mechanism that strengthens students’ entrepreneurial motivation.